Features of the survey of heat consumption in the development of a comprehensive plan for energy efficiency institution of higher education - Lagereva E.A. (Научно-технический вестник Брянского государственного университета)
The methodology of the survey of heat consumption in the development of a comprehensive plan for energy conserva-tion educational institutions of higher education. The results of field studies of heat consumption one of the educational institutions of the city of Bryansk. The survey was done study of the temperature and humidity and an air regimen of locations, a thermographic survey of the exterior enclosures of buildings, the analysis of the data of heat meters. Built valid temperature charts of the surveyed buildings, obtained by processing the experimental data using the least squares method. Graphs of actual and theoretical costs of TEP-lots daily during the whole heating period. Propose concrete actions, allowing to increase the efficiency of the heating system of the educational institution.